Knowledge regarding neonatal jaundice among a sample of mothers attending some Primary Health Care centers /Baghdad - Thabit , Maral F (Diyala Journal of Medicine, 2019)
Background: Neonatal jaundice is most common condition requiring medical evaluation in a newborn and it is yellowish discoloration of the white part of the eyes and skin in a newborn baby due to high bilirubin levels. Objective: To assess the knowledge regarding neonatal jaundice in a sample of mothers attending some Primary Health Care centers, Baghdad. Patients and Methods: A cross-sectional study was conducted including 265 mothers attending some primary health care centers in Baghdad during November and December 2016. They were subjected to previously structured questionnaire covering many aspects of neonatal jaundice distributed in 3 main domains and the mother's responses were gathered and then statistically analysed by frequency, percentages and percent score for each question responses and domain and the overall knowledge mean score. Results: Family and relatives were the main source of information 39.7% and the results revealed that the mean percent score for knowledge responses was 74% for definition of jaundice, 68% for complications of jaundice and 71% for ways of treatment.The mean overall percent score for knowledge was 71%. Conclusion: Good mean overall knowledge level regarding neonatal jaundice among study group.